Influence of organic additives with electron‐withdrawing and electron‐donating groups on insulation properties of cross‐linked polyethylene at high temperatures for HVDC cable applications. Issue 24 (22nd March 2022) - Shi, Yiwen; Chen, Xiangrong; Meng, Fan‐Bo; Awais, Muhammad; Hong, Zelin; Paramane, Ashish; Li, Hao
Abstract: This paper investigated the influence of three aromatic voltage stabilizers (4‐ n ‐propylbenzoic acid, 2‐methoxyphenylboronic acid, and 3‐aminobenzoylmethylamide) on insulating properties of cross‐linked polyethylene (XLPE) at high temperatures for high voltage direct current (HVDC) applications. The XLPE blends containing 1 wt% voltage stabilizers were prepared through a solution‐blending method. The addition of voltage stabilizers suppressed the space charge inside the XLPE at high temperatures. The DC conductivity of XLPE and its blends increased with temperature. The DC conductivity of the XLPE blended with the 4‐ n ‐propylbenzoic acid was lowest at the different temperatures and electric fields. The DC breakdown strength of the tested materials continually decreased as the temperature increased. Notably, the DC breakdown strength of XLPE with the addition of 4‐ n ‐propylbenzoic acid and 3‐aminobenzoylmethylamide was higher than the reference XLPE at high temperatures. Moreover, the thermal stability of the XLPE remained unaffected after the voltage stabilizer's addition, whereas the thermal conductivity was improved. Quantum chemical calculations showed that the addition of voltage stabilizers with lower LUMO could effectively buffer the high‐energy electrons and improve the DC breakdown strength of the XLPE. A buffering mechanism of high‐energy electrons demonstrated the effect of the voltage stabilizers on the DC breakdown strength in the XLPE. Abstract :